Ethnobotanical Significance and Antimicrobial Activity of Blumea lacera (Roxb.) DC - Mahajan, Ritu (International Journal of Pharmaceutical & Biological Archive, 2010)
The ethnobotanical significance and antimicrobial potential of various extracts of Blumea lacera was investigated. The plant was found to be used in many folk preparations. Antimicrobial potential of the plant was evaluated against three bacterial and one fungal species. Two different solvents - water and methanol were used for extraction purposes. Among the different extracts investigated, water extract of Blumea lacera was found to possess a broad spectrum of antimicrobial activity against studied bacterial strains. For the antifungal activity, both extracts of Blumea lacera showed promising results.